EVALUATIVE CONDITIONING WITH SUBLIMINAL PRESENTATIONS OF UNCONDITIONED STIMULUS. A EXPERIMENTAL STUDY - Campoy Menéndez, Guillermo; Romero Medina, Agustín; Martínez Sánchez, Francisco (Anales de Psicología / Annals of Psychology)
We study the possibility of establishing conditioned evaluative responses by subliminal Uss presentations. For that, we have carried out an experiment using neutral no-words like CSs and pleasant and unpleasant words like USs. The CS-US couples were showed three times, the USs being presented 28.57 msec. and with backward mask. Ours results show a mere exposure effect but not a evaluative conditioning one.